The influence of microstructure on electrical resistivity in palladium alloys - Lang, Candace Irene (Centre for Materials Engineering, 2016)
The relationship between microstructure and electrical resistivity has been studied in palladium-tungsten and palladium-molybdenum alloys, which exhibit an anomalous increase in resistivity after annealing. The effect of dislocations and structural order on resistivity has been investigated in order to determine the mechanisms whereby changes in resistivity occur in these alloys. The electrical resistivity of palladium-tungsten and palladium-molybdenum alloys has been determined as a function of annealing temperature, using a sensitive electronic apparatus purpose-designed for the present work. For alloys of low solute concentration a minimum in the electrical resistivity with respect to annealing temperature, which has not previously been reported, was observed. Specimens subjected to annealing experiments have been studied by means of transmission electron microscopy, in order to determine the effect of annealing on microstructure and structural order. The information obtained bas been used to relate the measured changes in electrical resistance and microhardness to the structural evolution of the alloys. It is concluded that the unusual resistance effects observed arise from competition between changing degrees of structural order and dislocation density. Which of these mechanisms predominates under given conditions varies as a function of solute concentration and annealing temperature. In alloys containing more than 6 at.% solute, recovery and recrystallisation processes are accompanied by an increase in resistivity and a decrease in microhardness; after recrystallisation is complete, further annealing bas no significant effect on either property. In alloys containing less than 6 at.% solute, recovery and recrystallisation are accompanied by a decrease in both resistivity and microhardness; but further annealing results in an increase in resistivity. Consideration of this data leads to the conclusion that microbardness is more sensitive to changes in dislocation density than structural order, whereas electrical resistivity is more sensitive to structural order than dislocation density. On this basis it is shown that short-range order increases rapidly at low annealing temperatures in alloys containing more than 6 at.% solute, but slowly in alloys containing less than 6 at.% solute in which short-range order increases rapidly only at higher annealing temperatures.